Processamento do alho negro - Pires, Liliane de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Garlic (Allium sativum) has excellent nutritional value, due to its vitamins content like A, B2, B6 and C, amino acids, enzymes, biologically active compounds and minerals like iron, zinc, selenium and iodine. The various health benefits are generally attributed to organosulfur compounds. Black garlic is obtained from raw garlic submitted to thermal treatment at controlled temperature and relative humidity for long time periods. The black color of the garlic is due to the Maillard reaction and consequent melanoidins formation, as product of the reaction between sugar and amino acids present in fresh garlic. Although some authors have reported that during the maturation process the amount of antioxidants increases, the manufacturing of black garlic is still very empirical and studies about this processing have not been sufficiently clarified in the literature. Thus, the objective of this study was to investigate the processing of black garlic by aging or maturation, assessing the influence of temperature and relative humidity on the nutritional and sensory quality, in order to select the best operation conditions. For this purpose, garlic bulbs were exposed to atmospheres with controlled relative humidity by means of saturated salt solutions of NaCl and KCl, and three levels of temperatures (65 °C, 72.5 °C and 80 °C). Drying curves was determined by weighing the samples periodically. The diffusion equation adequately represented the moisture variation during the aging of garlic at 80 °C, whereas the 72.5 °C it was reasonable, and at 65 °C was less efficient. Occurred considerable temperature influence on diffusivity, which ranged from 2.4310-11 to 1.2710-10 m2/s, between the temperatures of 65 and 80 °C, when aged at ambient conditioned by saturated solution of NaCl, and the 1.5210-11 to 6.9210- 11 m2/s, between the same temperatures, with saturated solution of KCl. Influences of temperature, relative humidity and ...

O alho (Allium sativum) possui excelente valor nutricional, contendo em sua composição vitaminas do tipo A, B2, B6 e C, aminoácidos, enzimas, compostos biologicamente ativos e minerais como ferro, zinco, selênio e iodo. Seus diversos benefícios à saúde são geralmente atribuídos à presença de compostos organosulfurosos. O alho negro é produzido a partir do alho cru através da aplicação de tratamento térmico em temperatura e umidade relativa controlada, por longos períodos de tempo. A coloração negra do alho se deve à reação de Maillard e consequente formação de melanoidinas, produto da reação entre o açúcar e os aminoácidos presentes no alho fresco. Apesar de alguns autores reportarem que durante o processo de maturação a quantidade de antioxidantes é aumentada, a fabricação do alho negro se apresenta ainda muito empírica e estudos sobre seu processamento não estão bem esclarecidos na literatura. Diante disso, o objetivo do presente trabalho foi investigar o processamento do alho negro por envelhecimento ou maturação, avaliando a influência da temperatura e umidade relativa sobre sua qualidade nutricional e sensorial, com o intuito de selecionar as melhores condições operacionais. Para tanto, bulbos de alhos foram expostos a atmosferas com umidade relativa controlada por meio de soluções salinas saturadas de NaCl e KCl, em três níveis de temperatura (65 °C, 72,5 °C e 80 °C). Curvas de desidratação foram determinadas por pesagens periódicas das amostras. A equação de difusão foi capaz de representar bem a variação de umidade durante o envelhecimento do alho a 80 °C, enquanto que a 72,5 °C o modelo foi razoável e a 65 °C foi pouco eficiente. Constatou-se considerável dependência da difusividade com a temperatura, que variou de 2,4310-11 a 1,2710-10 m2s-1, entre as temperaturas de 65 e 80 °C, quando envelhecido em ambiente condicionado por solução saturada de NaCl, e de ...
Keywords: Tecnologia de alimentos; Alimentos - Conservação - Tratamento térmico; Alho - Secagem; Alho negro Processamento; Antioxidantes; Fenóis; Difusividade termica; Temperatura atmosferica; Food Technology